Determinants of medication adherence among adults with type 2 diabetes mellitus in three Malaysian public health clinics: a cross-sectional study - Chew BH; Hassan NH; Sherina MS (Patient Preference and Adherence, 2015)
Boon-How Chew,1 Noor-Hasliza Hassan,2 Mohd-Sidik Sherina3 1Department of Family Medicine, Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2Klinik Kesihatan Dengkil, Ministry of Health, 3Department of Psychiatry, Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, Serdang, Malaysia Abstract: Medication adherence (MA) in adults with type 2 diabetes mellitus (T2D) is associated with improved disease control (glycated hemoglobin, blood pressure, and lipid profile), lower rates of death and diabetes-related complications, increased quality of life, and decreased health care resource utilization. However, there is a paucity of data on the effect of diabetes-related distress, depression, and health-related quality of life on MA. This study examined factors associated with MA in adults with T2D at the primary care level. This was a cross-sectional study conducted in three Malaysian public health clinics, where adults with T2D were recruited consecutively in 2013. We used the 8-item Morisky Medication Adherence Scale (MMAS-8) to assess MA as the main dependent variable. In addition to sociodemographic data, we included diabetes-related distress, depressive symptoms, and health-related quality of life as independent variables. Independent association between the MMAS-8 score and its determinants was done using generalized linear models with a gamma distribution and log link function. The participant response rate was 93.1% (700/752). The majority were female (52.8%), Malay (52.9%), and married (79.1%). About 43% of patients were classified as showing low MA (MMAS-8 score <6). Higher income (adjusted odds ratio 0.90) and depressive symptoms (adjusted odds ratio 0.99) were significant independent determinants of medication non-adherence in young adults with T2D. Low MA in adults with T2D is a prevalent problem. Thus, primary health care providers in public health clinics should focus on MA counselling for adult T2D patients who are younger, have a higher income, and symptoms of depression. Keywords: medication adherence, type 2 diabetes mellitus, quality of life, distress, depression, primary care